Onemitev in oslabitev samoglasnikov v kroparskem govoru - Škofic, Jožica (Slavistična revija, 1996)
The paper presents modern vowel reducation in the local dialect of Kropa in Upper Carniola. Like other Upper Carniolan dialects, this dialect displays extensive vowel reduction, i.e., in the form of weakening of short stressed vowels (to schwa) or as weakening and loss of short unstressed vowels, which are reduced in pre-tonic and post-tonic syllables, in the word-final position, and in clitics. The most commonly reduced vowel is /i/, the rest of them are reduced to a somewhat lesser extent. Some consonant clusters with a sonorant resulting from the vowel loss then disintegrate (into schwa + sonorant).
Keywords: dialect; dialectology; dialektologija; glasoslovje; kroparski govor; narečja; Phonetic sciences; redukcija; samoglasniki; Slovene; slovenščina